Comparative analysis of structural characteristics of soil insects in beech ecosystem in „Mavrovo“ National Park and oak ecosystems in Macedonia - Prelik, Dana (Macedonian Journal of Ecology and Environment, 2003)
In this paper were presented comparative analysis of structural characteristics of soil insects in beech ecosystem in „Mavrovo“ National Park and Quercetum frainetto- cerris ecosystems in Macedonia. The investigation of structural features of soil insects in the whole investigated profile and separately in the forest floor and soil layers of 0-5 cm and 5-10 cm depth has been done through out examination of structural characteristics such as: index of richness (d), diversity (H’) and homogeneity J(e). There have been determined similar oscillations of richness (d) and diversity (H’) values, but only between layers of 0-5 cm and 5-10 cm depth and forest floor and layer of 5-10 cm depth. Index of homogeneity J(e) vary in tighter frames and appears out statistically significant differences at 95% confidence level, but only between the forest floor and the soil layers of 5-1- cm depth. There are significant differences of structural characteristics of sol insects, evidenced by comparative analyze, due to differences of ecological conditions in those forest ecosystems.